While the Meter is Running: Computing in a Capped World - Chetty, Marshini; Banks, Richard; Brush, A.J.; Donner, Jonathan; Grinter, Rebecca E. (Interactions, 2011)
What happens when your Internet use is palpably constrained? What happens when you only have a fixed amount of bandwidth per month and where every byte you access uses up this precious resource? Or worse, what happens when you have to share that bandwidth pool with the three other Internet users in your household? These are the questions raised when we begin thinking about how users interact with the Internet in metered bandwidth situations. By answering these questions, we can help Web developers, interaction and application designers, and even Internet service providers (ISPs) customize their experiences for situations in which each byte delivered has a monetary value. In this article, we report initial insights from our experiences studying how households in South Africa use metered bandwidth.